Eczema: tactics of choice external therapy - D. V. Zaslavsky; Е. S. Tulenkova; K. N. Monakhov; N. A. Kholodilova; Yu. S. Kondratieva; O. B. Tamrazova; O. В. Nemchaninova; M. O. Guliev; I. L. Shlivko; I. Е. Torshina (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The therapeutic effects of synthetic tannins are based on their binding action, as well as on their anti-pruritic, antimicrobial and anti-inflammatory effects. Materials and methods. A clinical study of Neotanin spray, Neotanin lotion (suspension) and Neotanin cream was carried out in 8 clinical centres during the period from June, 2017 to January, 2018. The study had an open and non-comparative character. The study included 68 patients of both sex es aged from 1 month to 80 years suffering from eczema dermatosis in the acute weeping phase, including cases with complications after secondary infections (including eczema elements localized on the face). Before the study, information on the clinical history, demographic data, co-morbidities, physical examination data of the patients was collected. The treatment regimen included 2 stages: 1) Neotanin in the spray or lotion (suspension) form 3-4 times per day during 1-5 days, up to the full drying of eczema elements; 2) Neotanin in the cream form 3 times per day, up to the disappearance of the clinical manifestations of skin dermatosis. The duration of the study ranged from 5 to 14 days: the study was completed when a patient had achieved remission. The criteria for assessing the drug efficacy were as follows: dynamics of subjective complaints, objective assessment of the patient's condition (the presence and severity of clinical symptoms), dynamics of the Dermatology Life Quality Index (DLQI). Results. Neotanin preparations showed a high efficacy in the acute and subacute stages of the inflammatory process as an antipruritic agent. Itching stopped within 5 minutes after the drug application, with the antipruritic effect lasting for an average of 3-4 hours. In 85 % of the patients, marked excoriations were absent on the 3rd day of treatment. Neotanin demonstrated a pronounced anti-inflammatory effect. In 92 % of the patients, the symptoms of erythema and edema were significantly reduced one week after the beginning of treatment, with the manifestations of inflammatory exudation being conclusively decreased. One week following the beginning of treatment, 100 % of the patients demonstrated no oozing lesions. The absence of serious undesirable effects in the patients during the study evidences to the good tolerability and safety of this drug.